The Analysis of Code-switching in Maudy Ayunda’s YouTube Podcast - Sherren Graciela Putri Violeta (Fakultas Ilmu Budaya, 2025)
This study aims to analyze the types and the reasons for using code-switching used by Maudy Ayunda and Najwa Shihab in a podcast entitled Buka Kartu: Ternyata Najwa Shihab dan Maudy Ayunda juga BUCIN! The data of this research are utterances that contain Indonesian and English, thus this study belongs to qualitative research. This research employs Poplack’s (1980) classification of code-switching types and Hoffmann’s (1991) propositions of reasons of using code-switching. The result shows that all three types of code-switching are found. They comprise intra-sentential switching (59 data), inter-sentential switching (25 data), and tag switching (6 data). Further, the analysis reveals that there are 8 reasons found. They consist of talking about a particular topic (46 data), quoting somebody else (2 data), being emphatic about something (14 data), interjection (6 data), repetitions used for clarification (2 data), intention of clarifying speech content for interlocutor (16 data), expressing group identity (3 data), and repetition well as intention (1 data).
Reapload File Repository 6 Februari 2026 Maya/Mita
Keywords: code-switching; podcast